Dual role of peripheral B cells in multiple sclerosis: emerging remote players in demyelination and novel diagnostic biomarkers - Torres Iglesias, Gabriel; Fernández-Fournier, Mireya; López-Molina, MariPaz; Piniella, Dolores; Laso-García, Fernando; Gómez-de Frutos, Mari Carmen; Alonso-López, Elisa; Botella, Lucía; Chamorro, Beatriz; Sánchez-Velasco, Sara; Puertas, Inmaculada; Tallón Barranco, Antonio; et al. (Frontiers in Immunology, 2023)
Introduction: Multiple sclerosis is an inflammatory and demyelinating disease caused by a pathogenic immune response against the myelin sheath surfaces of oligodendrocytes. The demyelination has been classically associated with pathogenic B cells residing in the central nervous system that release autoreactive antibodies against myelin. The aim of the present study was to investigate whether extracellular vesicles (EVs) mediate delivery of myelin autoreactive antibodies from peripheral B cells against oligodendrocytes in multiple sclerosis (MS) and to analyze whether these EVs could mediate demyelination in vitro. We also studied the role of these EV-derived myelin antibodies as a diagnostic biomarker in MS. Methods: This is a prospective, observational, and single-center study that includes 2 patients with MS and two control groups: patients with non-immune white matter lesions and heathy controls. We isolated B-cell-derived EVs from the blood and cerebrospinal fluid (CSF) and analyzed their myelin antibody content. We also studied whether antibody-loaded EVs reach oligodendrocytes in patients with MS and the effect on demyelination of B-cell-derived EVs containing antibodies in vitro. Results: This study enrolled 136 MS patients, 23 white matter lesions controls, and 39 healthy controls. We found autoreactive myelin antibodies in EVs that were released by peripheral B cells, but not by populations of B cells resident in CSF. We also identified a cut-off of 3.95 ng/mL of myelin basic protein autoantibodies in EVs from peripheral B cells, with 95.2% sensitivity and 88.2% specificity, which allows us to differentiate MS patients from healthy controls. EV-derived myelin antibodies were also detected in the oligodendrocytes of MS patients. Myelin antibody-loaded EVs from B cells induced myelin markers decrease of oligodendrocytes in vitro. Discussion: Peripheral reactive immune cells could contribute remotely to MS pathogenesis by delivering myelin antibodies to oligodendrocytes. EV-derived myelin antibodies could play a role as diagnostic biomarker in MS.